Progressive Muscle Relaxation Reducing Blood Sugar Levels In Diabetes Mellitus Patients: Literature Review - Rochmah, Ardianti Fauziah; Muhith, Abdul; Zahro, Chilyatiz (Journal of Applied Nursing and Health, 2023)
Background: Diabetes will cause many complications if it is not treated properly. Complex treatment for people living with diabetes will cause a person to experience stress, so not many sufferers comply with treatment to control blood sugar levels. This literature review aims to determine the reduction in blood sugar levels in diabetes mellitus sufferers with progressive muscle relaxation. Methods: The method used in this article is a literature review using journal databases from Science Direct, PubMed, and Google Scholar in the 2020-2023 time period with the keywords "Progressive Muscle Relaxation or Relaxation Technique," "Blood sugar levels" and "Diabetes Mellitus Results: The results obtained were 2,111 articles. Articles were selected according to the criteria; the result was 19 articles ready to be reviewed. From the literature review study results, it was found that progressive muscle relaxation influences reducing blood sugar levels in diabetes mellitus sufferers. Progressive muscle relaxation can relax the body so that the parasympathetic nervous system will stimulate the secretion of the hormone insulin so that it can control blood sugar levels. Conclusion: It is hoped that people living with diabetes will increase their physical activity by doing progressive muscle relaxation twice a day to reduce blood sugar levels in diabetes mellitus sufferers.